(untitled) (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
This research will examine the internalization of the values ​​contained in the concepts of democracy and humanism in Islamic education. In this study, the author uses a qualitative method, so the data collection method is carried out by library research, while the analysis of the data and information that has been collected uses content analysis techniques. In essence, democracy and humanism are respect for human values, and an understanding that seeks to place humans as humans in accordance with their human nature. These values ​​are important to be implemented in Islamic education, both in curriculum development, learning strategies, teaching staff, evaluation systems, and the application of rewards and punishments. The implementation of the values ​​of humanism and democracy in education has great potential to realize the ideals of national education in order to build a generation of intellectual, emotional and spiritual intelligence, mental and tough spirit, creative and innovative and has the ability to find solutions to the problems of life that are being experienced.